Studi Analisa Rugi-Rugi Daya Dan Jatuh Tegangan Saluran Transmisi Tegangan 150 KV Pada Gardu Induk Padang Industrial Park Ke Gardu Induk Lubuk Alung - Gogo Prayogo; Yani Ridal; Chairul Nazallul A (Journal of Innovative and Creativity, 2025)
The electric power transmission system plays an important role in maintaining the continuity and quality of power delivery from generation plants to consumers. This study aims to analyze the magnitude of power losses and voltage drops on the 150 kV transmission line connecting the Padang Industrial Park Substation and the Lubuk Alung Substation. The method used is a descriptive quantitative approach through manual calculations based on 24-hour operational data collected on January 4, 2025. The main parameters observed include load current, sending-end voltage, line length (13.7 km), and conductor specifications of ACSR 240/40 mm. The analysis results show that the maximum power loss occurred at 19:00 WIB, amounting to 249.91 kW or 0.46% of the sending power, while the minimum power loss occurred at 07:00 WIB, amounting to 75.78 kW or 0.25%. The total energy loss over 24 hours was recorded at 2885.94 kWh, with an average power loss of 118.99 kW (0.32%). The maximum voltage drop occurred at 19:00 WIB at 1,077.87 volts (0.71%), while the average voltage drop was 734.41 volts (0.49%) relative to the nominal voltage. All values of power loss and voltage drop are below the 3% threshold according to SPLN No. 72 of 1987, indicating that the transmission line operates efficiently and reliably.